All the men of the Bible a portrait gallery and reference library of more than 3000 biblical characters - Lockyer, Herbert, 1886- (Grand Rapids, MI Zondervan, 1958)
Includes bibliographical references and index.
Brethren writer.
Keywords: Biblical men -- biography